2003
DOI: 10.1016/s0741-5214(03)00732-8
|View full text |Cite
|
Sign up to set email alerts
|

Failure of arteriovenous fistula maturation: an unintended consequence of exceeding Dialysis Outcome Quality Initiative guidelines for hemodialysis access

Abstract: Implementation of preoperative duplex US scanning and venography as a component of a more aggressive protocol to create native fistulas was pivotal in exceeding DOQI guidelines for hemodialysis access. However, this approach resulted in the unintended sequela of decreased fistula maturation rate. Our experience suggests that improved selection criteria based on findings at preoperative imaging are needed to further refine and optimize arteriovenous access surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
162
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(173 citation statements)
references
References 24 publications
8
162
2
1
Order By: Relevance
“…However, we strongly believe that endovascular treatment should be attempted before surgery is considered for the following reasons: (1) We and others (22)(23)(24)33) have demonstrated that endovascular treatment is associated with excellent success rates, low complication rates, and promising long-term patency rates (24). Most important, this is done without the introduction and assistance of synthetic polytetrafluroethylene grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we strongly believe that endovascular treatment should be attempted before surgery is considered for the following reasons: (1) We and others (22)(23)(24)33) have demonstrated that endovascular treatment is associated with excellent success rates, low complication rates, and promising long-term patency rates (24). Most important, this is done without the introduction and assistance of synthetic polytetrafluroethylene grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound or other means of preoperative venous mapping is likely to decrease the incidence of primary AVF failures (14 -19). However, the increasing demand to create more fistulas may lead to their creation in borderline vessels, thereby increasing primary failure rates (21)(22)(23). Thus, salvage of these primary failures will be essential for increasing AVF prevalence in the United States.…”
mentioning
confidence: 99%
“…Studies conflict regarding the association between women, AVF nonmaturation, and reduced patency (6)(7)(8)(9), which is hypothesized to be related to smaller diameter veins in women compared with men. This is difficult to assess, because many studies do not perform preoperative vein mapping or report vein diameters.…”
Section: Demographicsmentioning
confidence: 99%
“…Many variables should be considered (89,92,93), and using minimal vessel diameter as a sole criterion should be avoided. Doing so may preclude the use of veins that would have been acceptable by clinical examination (24,94). Furthermore, several recent studies demonstrated no significant association between vessel diameter and AVF primary failure (95).…”
Section: Continue Fistula First With Review and Reevaluation Of The 1mentioning
confidence: 99%